Rediseño y Automatización de un Molde para la Fabricación de Vitrinas Refrigeradas usando Inyección de Espuma de Poliuretano - Yime, Eugenio; Páez, Jheifer (Ingeniería, 2016)
Context: To stay competitive over time, a company must continually submit their processes to improvements and updates. Herein are proposed some improvements with regard to safety at work and the reduction of time that occurs during the operation of a mold for manufacturing refrigerators. Method: Some operating conditions of the mold are analyzed and then some factors affecting the processing time and the safety of operating personnel are established. The weaknesses found are related to the intrinsic design of the mold, which raises the need for a structural redesign that also includes automation. Results: It is presented a new design and way to operate the mold which reduces the risk of accidents at having no heavy loads over operator heads. Another contribution of the redesign is the increase in the system rigidity which helps to reduce manufacturing defects. Finally, it is show a automation design which helps to reduce manufacturing times. Conclusions: Significant improvements were obtained in the operation of the mold, such as the reduction of occupational hazards and reduced manufacturing time of refrigerators. These improvements translate into benefits for the company, by reducing costs and increasing production. Both benefits help strengthen the competitiveness of the company.